The Correlation Between Students’ Motivation in Learning English and Reading Comprehension at Sixth Semester Students of Medical Record Program - Deviga, Lidia; Ardhani, Radian Arum (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
The purpose of this research is to find the correlation between students’ motivation in learning English and reading comprehension at sixth semester students of medical record program. This research was a quantitative approach. The population of this research was two class in medical record program. (STIKES Bhakti Husada Mulia Madiun) Which consisted of 60 students. And then 30 students were selected as the sample using sampling technique.  The data of the students’ motivation in learning English were collected by using the questionnaire, while the data of students’ reading comprehension were collecting by reading comprehension test multiple choice. The result showed a correlation between students’ motivation in learning English (Variable X) and students’ reading comprehension (Variable Y). The result showed that there was a statistically significant correlation (0.756) is higher than the r value of significant level at 5 % (0.304). Theoretically, Null Hypothesis (Ho)is rejected and Alternative Hypothesis (Ha) is accepted. It meant that the students’ motivation in learning English contributed.